Early Detection of Changes in the Cardiovascular System in Patients with Diabetes (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In the article sugary to diabetes played patients heart blood vessel in the system harvest to be physiological processes about word goes - insulin secretion and effect or this two factor defect as a result come coming out and hyperglycemia with passing one group substances exchange breakdown disease (WHO 1999).